Synthesis of Biodegradable Superabsorbent Polymers from Carboxymethyl Cellulose/Humic Acid - Nurul Ismillayli; Siti Raudhatul Kamali; Surya Hadi; Dhony Hermanto (Acta Chimica Asiana, 2019)
Superabsorbent polymer (SAP) blend has been synthesized from carboxymethyl cellulose (CMC), humic acid, and aluminum sulphate octadecahydrate cross-linker. SAP is hydrophilic networks that can absorb and retain huge amount of water within their structures. Humic acid as starting material of polymer, was isolated from subgrade Batujai Dam by using IHSS method. Water Absorption Capacity (WAC) measurement, FTIR analysis, and agitation tests to investigate the cross-linking process and which of Al3+ and SO42- ions causes the crosslinking are carried out. Optimum cross-linking ratio of CMC and cross-linker appeared to be 2wt% corresponded to WAC determination. FTIR spectrum of CMC/humic acid blend and agitation test showed that CMC react with humic acid during polymerization process via Al3+ ion. Keywords: carboxymethyl cellulose; Al3+ ion; humic acid; superabsorbent polymer.